2022
DOI: 10.3389/fpubh.2022.793702
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Sexual Behavior and Partner Notification for Sexually Transmitted Infections Between the Out of School Youth and University Students in a Peri-Urban District in South Africa—A Cross-Sectional Survey

Abstract: The increase in sexually transmitted infections (STIs) in young people is a public health concern. Among those in university and out of school, different contextual factors contribute to their risky sexual behavior and increased susceptibility to STIs and HIV. There are limited comparative studies examining risky sexual behavior and partner notification (PN) between these two groups, particularly in South Africa. We investigated sexual behaviors, self-reported STI diagnosis, health seeking behavior, and prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…With respect to the use of condoms, a higher proportion (54.2%) of the youths in the rural areas did not use condoms at their last sexual activity than their urban counterpart. This was in line with a study among youths in South Africa that found that (45.7%) of the participants did not use condom during their last sexual intercourse, more (56.0%) of the out of school youth compared to their counterparts (44.0%) [35]. A lower proportion was found in a study in Osun state that found that only 34% of them reported using a condom for the first time; half of them were from rural areas and the other half were from cities (p = 0.003); the prevalence was higher (45.1%) during the most recent sex [36].…”
Section: Discussionsupporting
confidence: 91%
“…With respect to the use of condoms, a higher proportion (54.2%) of the youths in the rural areas did not use condoms at their last sexual activity than their urban counterpart. This was in line with a study among youths in South Africa that found that (45.7%) of the participants did not use condom during their last sexual intercourse, more (56.0%) of the out of school youth compared to their counterparts (44.0%) [35]. A lower proportion was found in a study in Osun state that found that only 34% of them reported using a condom for the first time; half of them were from rural areas and the other half were from cities (p = 0.003); the prevalence was higher (45.1%) during the most recent sex [36].…”
Section: Discussionsupporting
confidence: 91%
“…Our result is consistent with previous studies. [24][25][26][27] This finding could be ascribed to the fact that testing for HIV in the health facility could also provide opportunities for AGYW to report other STIs that they could be suffering from. 27 28 Open access prevention interventions into the national HIV prevention programmes.…”
Section: Discussionmentioning
confidence: 99%
“…The reproductive health of young students is important; it not only affects the healthy growth of students, the safety and stability of schools, and the well-being of families but also directly affects a country's future development [23]. Owing to the low capacity for safe sex among young people, the incidence of unwanted pregnancies, induced abortion, sexually transmitted diseases, and serious damage to reproductive health among young people has increased significantly [24][25][26]. This not only affects their physical and mental health but also brings great pressure on social security and stability.…”
Section: Discussionmentioning
confidence: 99%